2020
DOI: 10.1155/2020/7157248
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Enterprise Competitiveness in Multiplex Networks of Standards: A Case Study of the Communication Industry in China

Abstract: Competing to set industry standards is a strategic option to a variety of industries. This paper aims to investigate the role of standard drafting in the evolution of enterprises’ competitiveness in multiplex networks of standards. Specifically, network-based measurements are deliberately designed to evaluate the enterprises participation, contribution, and collaboration in drafting standards. By demonstrating the development of the standard system in China’s communication industry, the effectiveness of our me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…China's education construction and development should keep pace with the times, keep pace with the times [1]. Online education is an indispensable form of education in the new era of society, which can not only maximize the utilization of social education resources, facilitate people to start professional knowledge learning online at any time but also enrich the service category of the education industry, drive the stable and sustainable development of education and economic construction [2][3][4]. Online vocational education institutions want to attract and cultivate more loyal learning experience users, in addition to improving the level of online education and comprehensive service level, but must also be innovative to improve their brand communication marketing work [5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…China's education construction and development should keep pace with the times, keep pace with the times [1]. Online education is an indispensable form of education in the new era of society, which can not only maximize the utilization of social education resources, facilitate people to start professional knowledge learning online at any time but also enrich the service category of the education industry, drive the stable and sustainable development of education and economic construction [2][3][4]. Online vocational education institutions want to attract and cultivate more loyal learning experience users, in addition to improving the level of online education and comprehensive service level, but must also be innovative to improve their brand communication marketing work [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Donghai Li. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] …”
unclassified
“…In developed countries and region such as the United States and Europe, most national standards are formulated by enterprises. However, in China, standards are mainly drafted by state-owned research institutes (F. Chen and Wei, 2020), with less enterprise participation, and the speed of standards formulation and revision cannot keep up with the needs of market changes and industrial development. Y. found that most influential drafting units are research institutes rather than enterprise.…”
Section: Introductionmentioning
confidence: 99%
“…The survival and development of enterprises depend largely on the results of standards competition (Narayanan and Chen, 2012). Enterprises increase their participation in standards formulation and increase their capital and human investment in standards setting, which is conducive to breaking the single and homogeneous situation of product technology, accelerating technological innovation and industrial upgrading, and gaining opportunity in a modern economy with rapid technological upgrading (F. Chen and Wei, 2020). Enterprises are the main body of the market and of standardization work; therefore, standardization activities cannot be separated from the participation of enterprises (He and Fang, 2011).…”
Section: Introductionmentioning
confidence: 99%